2000
DOI: 10.1046/j.1525-1594.2000.06550.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyzed Strong Acid Aqueous Solution Irrigation Promotes Wound Healing in a Burn Wound Model

Abstract: The purpose of the study was to understand the effectiveness of electrolyzed strong acid aqueous solution (ESAAS) for acceleration of epithelialization in a rat burn wound model. Eighteen anesthetized Sprague-Dawley rats received 30% total body surface area third-degree burns, and 2 days after injury, the wound eschars were removed. Rats were divided into 3 groups: Group 1, no irrigation; Group 2, irrigation with physiological saline; and Group 3, irrigation with ESAAS. Wounds were observed macroscopically unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
1
16
0
1
Order By: Relevance
“…Consistently, the microbicidal activities of EOWs were also completely abolished in our study after addition of 20% BSA to the test solutions. Indeed, the rapid inactivation of the anti‐microbial activity following contact with organic matter is the main disadvantage of the application of EOWs (Nakae and Inaba, 2000; Shimmura et al., 2000). Thus, to ensure the efficacy of disinfection procedures using EOW, a thorough pre‐cleaning to minimize the organic load present is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the microbicidal activities of EOWs were also completely abolished in our study after addition of 20% BSA to the test solutions. Indeed, the rapid inactivation of the anti‐microbial activity following contact with organic matter is the main disadvantage of the application of EOWs (Nakae and Inaba, 2000; Shimmura et al., 2000). Thus, to ensure the efficacy of disinfection procedures using EOW, a thorough pre‐cleaning to minimize the organic load present is essential.…”
Section: Discussionmentioning
confidence: 99%
“…ECAS a treatment significantly improved the survival rates within a rodent in vivo burn wound model infected with P. aeruginosa, along with a reduction in serum endotoxin levels [110]. Moreover, acidic ECAS a have been found to promote re-epithelisation (in an in vivo burn wound model), increasing the proliferation of lymphocytes and macrophages associated with dense collagen deposition [111]. The clinical evidence for the use of ECAS a is largely based on small-scale case studies, but it has shown promise in reducing bacterial infections in burn wounds [112], for the treatment of refractory chronic ulcers [109], as well as synergistic necrotising infections [113], and a neutralised ECAS is now commercially available specifically for the treatment of wounds (Dermacyn, Oculus Innovative Sciences, Petaluma, CA, USA [114]).…”
Section: (I) Treatment and Prevention Of Wound Infectionmentioning
confidence: 97%
“…Five commonly used topical agents are 5% mafenide acetate, 10% povidone with 1% free iodine, 0.25% sodium hypochlorite, 3% hydrogen peroxide, and 0.25% acetic acid [25]. In addition, hyaluronic acid was used for wound dressing [26]. Basically, modulation of nutrition, underlining medical problems (such as vascular and neural diseases, diabetes, and infection), acidity of wounds, host immunity, cytokines, NO, or prostaglandins have a great impact on wound healing process.…”
Section: Pathophysiology Of Wound Healingmentioning
confidence: 99%